أثر القيادة التحويلية في تحقيق الميزة التنافسية للمؤسسة دراسة حالة بمديرية الصيانة لمؤسسة سوناطراك ببسكرة - بزقراري, عبلة; مجنح, عتيقة (جامعة الوادي - University of Eloued, 2017)
قياس أثر القيادة التحويلية في تحقيق الميزة التنافسية بمديرية الصيانة لمؤسسة سوناطراك ببسكرة، ولتحقيق أهداف الدراسة صممت استمارة ووزعت على عينة عشوائية من المسيرين في المؤسسة البالغة 30 استبيان، وتم استرجاعها كلها كما كانت صالحة للتحليل والدراسة، حيث تم تحليل البيانات واختبار الفرضيات باستخدام برنامج SPSS، وقد توصلت الدراسة إلى عدة نتائج، حيث هناك تطبيق لنمط القيادة التحويلية بمستوى مرتفع حسب عينة الدراسة حيث بلغ المتوسط الحسابي (4,07) بمستوى موافق، كما أن أغلب أفراد عينة البحث متفقون على توافر أبعاد الميزة التنافسية في المؤسسة بمتوسط حسابي (3,70) بمستوى موافق. وتوصلت الدراسة إلى وجود أثر ذو دلالة إحصائية للقيادة التحويلية في تحقيق المرونة، والإبداع للمؤسسة محل الدراسة، ولكن بينت النتائج بأنه لا يوجد أثر معنوي للقيادة التحويلية في تخفيض التكلفة للمؤسسة، وتحسين الجودة، وسرعة التسليم. The study aimed to measure the impact of transformational leadership in achieving competitive advantage at Directorate of Maintenance Corporation Sonatrach in Biskra. To achieve the objectives of the study the researcher was designed and distributed to a Random sample of 30 managers in the organization, and she retrieved all questionnaire. The data were analyzed using SPSS program. The study found many results, that there is high application of transformational leadership according to a view of managers the mean equals (4.07), and so the most of the managers are agree on the availability of competitive advantage in the enterprise and the mean equals (3.70). In addition, the study found that there is significant effect of transformational leadership in achieving flexibility, and creativity of the enterprise under study, but the results showed that there was no significant effect of transformational leadership in the cost reduction, quality improvement, and fast delivery
The impact of transformational leadership in achieving competitive advantage at Directorate of Maintenance Corporation Sonatrach in Biskra
مقال
Keywords: قيادة إدارية، قيادة تحويلية، ميزة تنافسية; Managerial leadership, transformational leadership, competitive advantage.